Kinetics of Degradation of Bisphenol A by Ozonization in Aqueous Solution - Hou, Jiacai; Ge, Yanan; Li, Yue; Yuan, Aihua; Zhao, Qinghua; Jia, Shouhua (Asian Journal of Chemistry, 2015)
The degradation of bisphenol A in aqueous solution by ozonization was investigated at the laboratory scale. The primary factors that influenced the removal efficiency of bisphenol A were investigated, including the pH, the initial concentration of bisphenol A, the ozone gas concentration and the reaction temperature. Ozone enabled the efficient removal of bisphenol A and the maximum removal efficiency was achieved at pH 7. An accurate kinetic model of the chemical reaction and mass transfer was described by an exponential relationship between the pseudo-first-order rate constant and the operational parameters. The intrinsic kinetic constants for the reaction of bisphenol A with ozone were also determined using a competitive kinetics method with phenol as a reference compound. The results revealed that the pH exerted a strong influence on the kinetic constants and that the rate constants increased exponentially from 3.27 × 103 M-1 s-1 to 1.23 × 109 M-1 s-1 as the pH was increased from 3 to 11, respectively.